2021
DOI: 10.1017/s0144686x21000544
|View full text |Cite
|
Sign up to set email alerts
|

Enacting citizenship through participation in a technological society: a longitudinal three-year study among people with dementia in Sweden

Abstract: The role of Everyday Technology (ET) use is presented as subsidiary or neutral in policy for age- and dementia-friendly communities; and yet, research suggests that older people, especially those with dementia, experience increased challenges using ET in their everyday lives. Through the lens of micro-citizenship, the study aims to deepen the knowledge about how use of ET outside the home, including portable ETs, relates to participation in places visited within public space among people with dementia over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Most of those results were quantitative and cross-sectional. Caregivers and/or people living with dementia reported using transportation services in different proportions across regions, countries, gender, and time: 22.4% use (United States, Biegel et al, 1993 ), 21.0% monthly use, 6.8%–37.4% across regions (United States, 1995, Harrow et al, 2004 ), 21.6% use for female caregivers compared to 12.7% of male caregivers (United States, Sun et al, 2008 ), 42.7% last 4 weeks use by wives of community-dwelling care recipients with dementia (Canada, Pedlar & Biegel, 1999 ), 51.8% use (China, 2018, Sun et al, 2022 ), 68.8% use in Sweden at inclusion, with the frequentation decreasing to 50.0% in Year 1 follow-up and 37.5% in Year 2 ( Gaber et al, 2021 ). Reasons for using services or not using services were not explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of those results were quantitative and cross-sectional. Caregivers and/or people living with dementia reported using transportation services in different proportions across regions, countries, gender, and time: 22.4% use (United States, Biegel et al, 1993 ), 21.0% monthly use, 6.8%–37.4% across regions (United States, 1995, Harrow et al, 2004 ), 21.6% use for female caregivers compared to 12.7% of male caregivers (United States, Sun et al, 2008 ), 42.7% last 4 weeks use by wives of community-dwelling care recipients with dementia (Canada, Pedlar & Biegel, 1999 ), 51.8% use (China, 2018, Sun et al, 2022 ), 68.8% use in Sweden at inclusion, with the frequentation decreasing to 50.0% in Year 1 follow-up and 37.5% in Year 2 ( Gaber et al, 2021 ). Reasons for using services or not using services were not explored.…”
Section: Resultsmentioning
confidence: 99%
“…The adequacy between service and the needs of a person can also change in time, better illustrated by longitudinal studies. Only one longitudinal study found a decrease in the use of transportation services by people living with dementia in time ( Gaber et al, 2021 ). Having a mixed-method project to explore the reasons for this decrease would have been interesting.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT-OUT questionnaire was developed with older adults living with and without dementia and an in-depth explanation of the development process in three languages (English, French, and Swedish) can be found elsewhere (Margot-Cattin et al, 2019). Earlier studies using the ACT-OUT questionnaire in different countries (Chaudhury et al, 2021) and in conjunction with other instruments (Gaber et al, 2021; Margot-Cattin et al, 2021; Wallcook et al, 2021) contribute to the validity of the ACT-OUT questionnaire. Further psychometric testing is underway.…”
Section: Methodsmentioning
confidence: 99%
“…The pandemic has underscored that a movement to counter the isolation and social exclusion that often accompany dementia is long overdue. Thoughtful design has a critical role to play; public places and services like transportation may be abandoned by PLWD when they are not designed to be dementia friendly [3]. Yet, it does need to be said that the social inclusion and rights of people living with dementia cannot be reduced to a technical problem.…”
Section: Design Questions From the Health Sciencesmentioning
confidence: 99%